2020
DOI: 10.1002/anie.202003560
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Lived Charge‐Transfer State Induced by Spin‐Orbit Charge Transfer Intersystem Crossing (SOCT‐ISC) in a Compact Spiro Electron Donor/Acceptor Dyad

Abstract: We prepared conceptually novel, fully rigid, spiro compact electron donor (Rhodamine B, lactam form, RB)/acceptor (naphthalimide; NI) orthogonal dyad to attain the long‐lived triplet charge‐transfer ( 3 CT) state, based on the electron spin control using spin‐orbit charge transfer intersystem crossing (SOCT‐ISC). Transient absorption (TA) spectra indicate the first charge separation (CS) takes place within 2.5 ps, subsequent SOCT‐ISC takes 8 ns to produce the 3 NI*… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
145
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(155 citation statements)
references
References 74 publications
(62 reference statements)
7
145
3
Order By: Relevance
“…[30] Because an orthogonal conformation between the two benzophenone units is always ensured in SFs,SOCT-ISC is believed to take place.Although this mechanism has been proposed and studied before,n o previous study has demonstrated systematic tunable ISC rate through engineering of the CT state. [21][22][23][24][25][26][27][28][29][30][31] Thecharge recombination rate constant (k CR )ork ISC were extracted from the global analysis and listed in Table 1. These results show that the k ISC of SF1-3 can vary by up to 2orders of magnitude in cyclohexane.Meanwhile, k ISC can also change by 2-3 orders of magnitude in SF2 and SF3 when the solvent is switched from cyclohexane to DMSO.…”
Section: Spin-orbit Charge Transfer Isc In Sf1-3mentioning
confidence: 99%
See 1 more Smart Citation
“…[30] Because an orthogonal conformation between the two benzophenone units is always ensured in SFs,SOCT-ISC is believed to take place.Although this mechanism has been proposed and studied before,n o previous study has demonstrated systematic tunable ISC rate through engineering of the CT state. [21][22][23][24][25][26][27][28][29][30][31] Thecharge recombination rate constant (k CR )ork ISC were extracted from the global analysis and listed in Table 1. These results show that the k ISC of SF1-3 can vary by up to 2orders of magnitude in cyclohexane.Meanwhile, k ISC can also change by 2-3 orders of magnitude in SF2 and SF3 when the solvent is switched from cyclohexane to DMSO.…”
Section: Spin-orbit Charge Transfer Isc In Sf1-3mentioning
confidence: 99%
“…[23] Recently,this mechanism has been applied to design as eries of orthogonal boron dipyrromethene (BOD-IPY)-based molecules as well as an orthogonal rhodamine/ naphthalimide dyad, with all of them exhibiting high triplet yields. [24][25][26][27][28][29][30][31][32][33] These previous studies have shown that both the CT state and the orthogonality of the MOs are critical for the efficient production of triplets via SOCT-ISC,h owever,o nly two studies demonstrated ISC in at ens of ps timescale. [32,33] Moreover,a ll previous systems featuring SOCT-ISC obey only one molecular design rule,i nw hich the electron donor and acceptor moieties are linked through as igma bond and the triplet state is generated in either the donor or the acceptor.T his is ad rawback for the ISC efficiency since the sigma bond allows for nearly free rotation between the donor and acceptor planes at room temperature.T his induces not only ground state heterogeneity that leads to uncontrollable degree of CT states but also facilitates alternative excited state deactivation pathways such as internal conversion through molecular twisting or direct charge recombination to the ground state.T hus,n ew molecular structures are needed to verify the universality of the SOCT-ISC mechanism and to elucidate the general rules regarding optimal molecular arrangement so that ultrafast SOCT-ISC and enhanced triplet generation quantum yields might be achieved.…”
Section: Introductionmentioning
confidence: 95%
“…[30] Because an orthogonal conformation between the two benzophenone units is always ensured in SFs,S OCT-ISC is believed to take place.A lthough this mechanism has been proposed and studied before,n o previous study has demonstrated systematic tunable ISC rate through engineering of the CT state. [21][22][23][24][25][26][27][28][29][30][31] Thecharge recombination rate constant (k CR )ork ISC were extracted from the global analysis and listed in Table 1. These results show that the k ISC of SF1-3 can vary by up to 2orders of magnitude in cyclohexane.Meanwhile, k ISC can also change by 2-3 orders of magnitude in SF2 and SF3 when the solvent is switched from cyclohexane to DMSO.…”
Section: Spin-orbit Charge Transfer Isc In Sf1-3mentioning
confidence: 99%
“…[23] Recently,this mechanism has been applied to design as eries of orthogonal boron dipyrromethene (BO-DIPY)-based molecules as well as an orthogonal rhodamine/ naphthalimide dyad, with all of them exhibiting high triplet yields. [24][25][26][27][28][29][30][31][32][33] These previous studies have shown that both the CT state and the orthogonality of the MOs are critical for the efficient production of triplets via SOCT-ISC,h owever,o nly two studies demonstrated ISC in at ens of ps timescale. [32,33] Moreover,a ll previous systems featuring SOCT-ISC obey only one molecular design rule,i nw hich the electron donor and acceptor moieties are linked through as igma bond and the triplet state is generated in either the donor or the acceptor.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation